2017
DOI: 10.3389/fendo.2017.00286
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Link Gonadotropin-Releasing Hormone Receptor Signaling Cascades in the Gonadotrope

Abstract: Biological rhythms lie at the center of regulatory schemes that control many aspects of living systems. At the cellular level, meaningful responses to external stimuli depend on propagation and quenching of a signal to maintain vigilance for subsequent stimulation or changes that serve to shape and modulate the response. The hypothalamus–pituitary–gonad endocrine axis that controls reproductive development and function relies on control through rhythmic stimulation. Central to this axis is the pulsatile stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 104 publications
1
7
1
Order By: Relevance
“…Besides, the potential advantage of evaluating PON-1 as a biomarker in the clinical diagnosis or treatment of oxidative stress was proposed [35]. Valkenburg et al, (2008) found in their study increased OS in PCOS women, which agreed with our result where the antioxidant PON1 activity was higher in the PCOS group to rebalance the higher OS [28], which may affect characteristics of embryos that correlate adversely with OS [36]. Proteomic analysis of follicular fluid documented 31 up-regulated proteins and 18 down-regulated proteins with different functions, only 5 of which have a function in the genital system.…”
Section: Resultssupporting
confidence: 86%
“…Besides, the potential advantage of evaluating PON-1 as a biomarker in the clinical diagnosis or treatment of oxidative stress was proposed [35]. Valkenburg et al, (2008) found in their study increased OS in PCOS women, which agreed with our result where the antioxidant PON1 activity was higher in the PCOS group to rebalance the higher OS [28], which may affect characteristics of embryos that correlate adversely with OS [36]. Proteomic analysis of follicular fluid documented 31 up-regulated proteins and 18 down-regulated proteins with different functions, only 5 of which have a function in the genital system.…”
Section: Resultssupporting
confidence: 86%
“…ROS generated by alcohol, smoking, or environmental factors might affect FSH synthesis (Zubair et al, 2017, Oremosu and Akang, 2015, Aprioku and Ugwu, 2016. Research has shown that ROS affects FSH's secretion via its effect on the gonadotropinreleasing hormone (Terasaka et al, 2017). This mechanism could not be corroborated in the present study.…”
Section: Associations Between Biomarkers Of Oxidative Stress/dna Damage and Reproductive Hormonescontrasting
confidence: 68%
“…In vivo, GnRH is pulsatile and elicits pulsatile secretion of LH 20 . A hallmark of gonadotropes is their ability to resolve signaling input from a GnRH pulse and reset for subsequent stimulation by a following pulse of GnRH 30 , 31 . Therefore, we examined whether GnRH-induced glycolysis is pulsatile with GnRH.…”
Section: Resultsmentioning
confidence: 99%